The Death of Oneself and the Meaning of Life in “Nero” by Miguel Torga - DE CASTRO SOARES, Maria Luísa; DE CASTRO SOARES, Maria João (Anafora, 2024)
The paper aims to analyze the tale “Nero,” from the work Bichos by Miguel Torga. In this work, some emphasis is firstly given to the relations of implication between the man, the environment, and the work of the poet originating from Trás‐os‐Montes, who gives voice to the Tellus Mater—that is, to “Mother Earth” (Feijó 167–84; Soares 293–303). Secondly, the work focuses on the questions of finitude and the meaning of life. In the form of an analepsis, an autodiegetic gaze of the partridge dog Nero turns to the past and, at the moment of its death, remembers the main events of its existence while recognizing that it was worth living. Written in 1940—to wit, in the context of the Portuguese dictatorship of the New State—the tale “Nero” thus alerts the reader to the value of life but also to its finitude and to the importance of building a meaningful existence, which transits through responsibility, freedom, the definition of goals, and personal choices.